Design of shading‐ and hotspot‐resistant shingled modules. (1st December 2021) - Clement, Carlos Enrico; Singh, Jai Prakash; Khoo, Yong Sheng; Halm, Andreas; Tune, Daniel; Birgersson, Erik
Abstract: The shingled module has become an attractive interconnection architecture for its higher packing density and superior power generation. However, with longer string lengths and smaller cell areas, these modules are particularly susceptible to developing hotspots from shading elements. In this paper, a framework for the design of hotspot‐ and shading‐resistant shingled modules is presented. An electrothermal model is developed and validated extensively through specially fabricated shingled modules that allow for string‐level measurement and analysis. To investigate the relative influence of cell electrical characteristics on power loss and hotspot temperature, we perform a stochastic Monte Carlo simulation which reveals a greater sensitivity to parameters associated with the shaded cell's leakage current. A further study on cells with illumination‐dependent J leakage shows the detriment of this light‐induced effect where higher hotspot temperatures can develop. Module‐level parameters are also investigated where string length, number of parallel strings, and cell fraction are studied in relation to their impact on module power and hotspot response. Finally, these findings are condensed into a design matrix which defines the space in which module manufacturers may configure shingled modules such that hotspots will not exceed a set threshold temperature. Abstract : With its longer string lengths and reduced cell areas, shingled modules are particularly susceptible to developing hotspots from small shading elements. In this paper, we perform comprehensive analyses on the effects of cell characteristics and module interconnection architecture on the shingled module shading response. The findings are used to create a design framework which defines the parametric space within which module manufacturers may produce shingled modules that are hotspot and shading resistant.